(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Given the conflict between human rights, namely health rights, and Intellectual Property Rights, which contributes to causing the access to drugs problem, this paper has the goal to formulate a feasible proposal for a patent law reform. Since the hierarchies of interests at stake in the intellectual property law system should be rebalanced, the paper puts forward a proposal, called Trading Time for Space (TTS). TTS provides a longer time for patent exclusive in western countries (Time) to the patent holder company, in exchange for the latter selling the drug at cost price in developing countries (Space).